2009
DOI: 10.1007/s10143-009-0185-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumefactive demyelinating lesions: nine cases and a review of the literature

Abstract: Tumefactive demyelinating lesions (TDLs) are misdiagnosed frequently. To investigate the characteristics of TDLs, clinical and radiological data from nine cases with TDLs were analyzed after admission. All cases underwent surgery and pathological examination; some received postoperative steroid therapy. Onsets were mostly within 3 weeks and main presentation included intracranial hypertension, extremity weakness, epilepsy, and visual disturbance. Symptoms in children were acute and severe, frequently including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
6
39
0
Order By: Relevance
“…However, our case may indicate that patients with TD should have a close and careful clinical follow-up with regard to concomitant or developing autoimmune or neoplastic disorder. In line with other reports [8,9], all lesions of our patient responded to dexamethasone. In unresponsive cases plasma exchange can be effective [10].…”
supporting
confidence: 94%
“…However, our case may indicate that patients with TD should have a close and careful clinical follow-up with regard to concomitant or developing autoimmune or neoplastic disorder. In line with other reports [8,9], all lesions of our patient responded to dexamethasone. In unresponsive cases plasma exchange can be effective [10].…”
supporting
confidence: 94%
“…Despite several reports [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], including some large series of tumefactive demyelinating disease [7,9,11,12], no consensus has been reached about this rare spectrum. Common MRI findings include single or multiple large white matter lesions with variable mass effect and edema, complete or open ring enhancement, T2W hypointense rim, and a perilesional restriction on DWI [9][10][11][12][13][14][15][16]. However the prevalence of these radiological features is highly variable, and it is still controversial whether tumefactive CNS IDD represent a variant of MS or a unique form of isolated demyelinating disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TDLs, often presenting with brain tumor mimicking clinical symptoms and space occupying lesions, have been described in previous reports [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, a variety of radiographic and clinical characteristics were reported in different studies; some emphasized the unifocal and clinically isolated features [7,8], while others highlighted the predominant multifocal lesions and a high trend of conversion into multiple sclerosis (MS) by follow-up [9,10].…”
Section: Introductionmentioning
confidence: 91%
“…Quick frozen sections are often misdiagnosed as astrocytoma because it is difficult to distinguish macrophages and swollen astrocytes. Therefore, Xia et al (19) suggested that intraoperative frozen section analysis was inconclusive in the diagnosis of intracranial demyelinating pseudotumor. Immunohistochemical techniques should be applied when the case is suspicious or uncertain (3).…”
Section: █ Discussionmentioning
confidence: 99%